Surface roughness modeling in chemically etched polishing of Si (100) using double disk magnetic abrasive finishing. Issue 5 (3rd September 2019) - Pandey, Kheelraj; Pandey, Pulak M.
Abstract: The present paper focuses on proposing a new method for determining the surface roughness of chemically etched polishing of Si (100) using double disk magnetic abrasive finishing (DDMAF). Based on chemical etching in KOH solution Vicker's hardness of Si (100) at different concentration of KOH was determined in context to chemical etching phenomenon. A mathematical relationship was established to relate Vicker's hardness of Si (100) as a function of the concentration of KOH. The penetration depth of abrasive particle into Si (100) workpiece was determined considering viz; the normal force acting on the abrasive particle under the influence of magnetic flux density and Vicker's hardness of etched Si (100). The other modeling variables such as wear constant, penetration area of the abrasive particle into Si (100) workpiece which is dependent on the penetration depth of abrasive particle was modified in terms of magnetic flux density and concentration of KOH. The process parameters such as working gap, abrasive mesh number and the rotational speed of the primary magnet were also considered in modeling the surface roughness. The results of surface roughness obtained by the model were also experimentally validated. The theoretical and experimental findings agreed well with each other.